Women's Leadership in the Era of Disruption (Case Study: Women's Leadership in Religious Organizations) - Eranutrise, Desmie; Baiduri, Ratih; Rosramadhana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Women as leaders must have an attitude that tends to be full of confidence, have a strong belief in their actions and be able to express their feelings and opinions without hurting their own feelings or the feelings of otherswithout interfering with the rights of others.Talking about women in terms of leadership, the position of women is often compared to the position of men in leadership before the modern era, women were often discriminated against in their position as leaders. However, with the development of the times, in this modern era there have been many women who are able to lead a group or organization. Women's leadership in the era of disruption or the digital era has now penetrated into public organizations, government, social organizations as well as into religious organizations. In this case the author will examine and see the leadership of women in a religious organization. The research method used in this research is descriptive qualitative research by conducting observations and literature studies (library research)